The narrative of ‘al-ghraniq al-‘ula’ in the qur’an: a myth or reality - Osmani, Noor Mohammad; Ali, Md. Yousuf (2015)
The story of ‘Al-Gharaneeq al-‘Ula’ or ‘prominent deities’ concerns about a historical narrative in the early stage of Islam. The Prophet Muhammad (pbuh) is reported to have recited the Surah an-Najm to a large group of Quraysh people, and reached the ayat 19-23, where he uttered the names of their ‘great deities’ such as Lat, Manat and ‘Uzza, he involuntarily recited تلك الغرانيق العلى، وإن شفاعتهن لترتجى “they are the prominent deities, and their intercession is much sought for”. This narrative caused a great havoc among the intellectual circles of the Qur’an and History. The historians, mufassirun and muhaddithun have cited this narrative in their books in details. This has led the readers of the Qur’an, Sunnah and the history of Islam into confusion. The narrative was used by the famous Orientalists like William Muir, Joseph Schacht and others as a tool to dissociate the Qur’an from the divine origin. The claim has also been made that the Prophet Muhammad (pbuh) was supportive of the pagan deities in the early stage of his mission as a way of getting closer to the Arab Mushriks. The scholars used three Qur’anic ayat for this purpose, which are: Surah An-Najm 19-23, Surah al-Isra 73-75 and Surah al-Hajj 52-54. A careful and closer reading of these Qur’anic ayat reveal the fact that the ayat were interpreted out of the contexts by the interpreters, historians and story tellers. The present research is carried out in order to discover the true fact behind this controversial incident. The research would deal with the incident and its credibility from historical, narrative, sanad and textual perspective to see if it carries some genuineness or is a total fabrication by some anti-Islamic forces to create doubt about the origin of the Qur’an. The study is a narrative, descriptive, analytical and critical one based on the original authentic literatures. It is expected that the article may come out with some clear insights which would help to remove confusion about the incident and the ayat to a large extent.